MARITIME ENGLISH IN FOCUS: A RATER-BASED EVALUATION OF ESP COURSEBOOK QUALITY - Yusi Rahmawati; Sri Wuli Fitriati; Widhiyanto; Sri Wahyuni (Universitas PGRI Palembang, 2025)
This study assesses the quality of a Maritime English coursebook used in a leading vocational maritime education program in Indonesia. The evaluation is based on expert opinions and criteria drawn from English for Specific Purposes (ESP) principles. A qualitative descriptive method was used, supported by document analysis. Data were collected from four expert raters using a 48-item Likert scale evaluation sheet. The analysis was done manually, focusing on item trends and using thematic categorization based on ESP indicators. The coursebook is considered relevant to maritime contexts, with strengths in vocabulary use and realistic tasks. However, it shows inconsistency in instructional design and does not fully align with learner-centered approaches expected in ESP materials. The findings are useful for maritime education, ESP material development, vocational curriculum design, and coursebook evaluation in applied linguistics, maritime training centers, and language education programs. This study also presents an expert-based evaluation framework for ESP coursebooks in maritime settings, addressing the lack of research using qualitative analysis based on expert judgment rather than student feedback.